Effect of acupuncture for disorders of consciousness in patients with stroke: A systematic review and meta-analysis - Huang, Zhibin; Chen, Yuning; Xiao, Qilan; Kuang, Weichuan; Liu, Kun; Jiang, Ye; Wen, Xi; Qin, Weiting; Liu, Yue; Liu, Tong (Frontiers in Neurology, 2022)
Background: Disorder of consciousness (DOC) are frequent in stroke, which is the second commonest cause of death and the crucial cause of disablement. Acupuncture has been used as a curative method for DOC treatment in China. Nevertheless, no critical systematic review concerning the effect of acupuncture for DOC have been published. The purpose of this review is to evaluate the present evidence respecting the efficacy of acupuncture for DOC after stroke. Methods: 7 databases were searched from their inception to November 1, 2021, containing 3 English databases (PubMed, Embase, Cochrane Central Register of Controlled Trials) and 4 Chinese databases (CNKI, CBM, VIP, and Wanfang Database). The primary outcome comprises Glasgow Coma Scale (GCS) and Glasgow Outcome Scale (GOS) before and after treatment. Secondary outcomes involves resuscitation rate, resuscitation time and adverse events. Data synthesis was calculated by RevMan (V.5.4.1) software. Methodological quality was assessed with the risk of bias according to Cochrane Handbook. Results: 17 studies containing 1143 patients were eventually included in our review. Overall, most trials were of poor quality. Only 2 were evaluated as having a low risk of bias. GCS was reported in 16 trials and meta-analysis showed that GCS improvement in acupuncture group was higher than non-acupuncture group (WMD 1.45, 95%CI 0.94 to 1.97, P<0.00001＝. 1 trial reported that GOS improvement in acupuncture plus medication group was higher than medication group (WMD 0.58, 95%CI 0.11 to 1.05, P=0.01). Another study reported that acupuncture plus medication was statistically more effective in shortening resuscitation time than medication alone (WMD -0.89, 95%CI -1.53 to -0.25, P=0.006). 4 trials reported that resuscitation rate in acupuncture group was higher than that without acupuncture intervention (WMD 3.34, 95%CI 1.87 to 5.95, P＜0.0001). Adverse events were reported in 2 studies with 1 case in acupuncture group suffering from subcutaneous hematoma, respectively. Conclusion: Acupuncture may be effective in improving consciousness level, increasing resuscitation rate, shortening resuscitation time for patients with DOC after stroke. Adverse events of acupuncture were rare, tolerable, and recoverable. However, the results should be interpreted with caution and more rigorous RCTs with better methodology are warranted.